Модель управления инновационным процессом на основе принципов менеджмента качества (Путеводитель предпринимателя, 2020)
Transition to innovative economy has caused creation of new models of management by the organisations and their innovative processes. The management model by innovative process by working out and realisation of pulse strategy of development is offered. The principles of system of a quality management put at the heart of model allow to support an impulse of development at the expense of full satisfaction of all participants of innovative process.